Portal rekrutmen berbasis web dengan seleksi transparan metode first come first served - Zulfahmi Indra; Nafil Rizq Trianto; Augis Dinanti; Khairany Zuhriyyah Jinan Hsb; Muhammad Iqbal Fahrezzi (Griya Journal of Mathematics Education and Application, 2025)
The advancement of information technology has accelerated digital transformation in various sectors, including job vacancy management and distribution systems. Manual registration processes often cause issues such as data duplication, delayed information delivery, and inefficiency. This study aims to design and implement a web-based job vacancy information system that applies the First Come First Served (FCFS) method as the registration and applicant selection mechanism. The system was developed using the Waterfall model, with PHP as the programming language and MySQL as the database management system. System testing focused on functional suitability, usability, and performance efficiency. The results indicate that the system successfully manages registration processes fairly and transparently based on submission order while improving overall efficiency and user experience. This research contributes to the development of an integrated and accessible employment information system that supports digital transformation in workforce management.